Utilizing Augmented Reality Media to Enhance Students’ Lathe Learning Outcomes - Ariansyah Ariansyah; Febri Prasetya; Purwantono Purwantono; Randi Purnama Putra (Jurnal Vokasi Mekanika (VoMek), 2025)
The integration of technology in vocational education has become a critical need to support 21st-century skills, especially in practice-based learning such as Basic Mechanical Engineering subjects. One promising innovation is the use of Augmented Reality (AR) media, which enables interactive three-dimensional visualization to help students concretely understand abstract concepts. This study aims to examine the effectiveness of lathe-based AR media in improving student learning outcomes and motivation in Grade X of the Machining Engineering Department at SMK Semen Padang. The research employed a quasi-experimental method using a non-equivalent control group design. The subjects consisted of two classes: the experimental class (using AR media) and the control class (using conventional learning methods). Data were collected using pre-tests and post-tests to assess learning outcomes and Likert-scale questionnaires to evaluate learning motivation. The analysis results showed that the use of AR media significantly increased student learning outcomes and motivation compared to traditional methods. Based on hypothesis testing and normalized gain score analysis, the AR media was found to be highly effective in the learning process. In conclusion, lathe-based Augmented Reality media proved to be an effective interactive learning tool that enhances students' academic performance and motivation, while also contributing to the development of innovative media in technical education.